Evaluation of Sports Ads Value Based on Consumer Psychology - Zhuo Bian, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
The effective dissemination of ads information can stimulate consumers’ desire to purchase sports products/services. In return, the purchases by consumers reflect the effectiveness of media dissemination of sports ads. Currently, there is not yet an index system or evaluation model for accurate evaluation of sports ads value. The relevant research of ads value is detached from consumers’ willingness to buy and purchases. Therefore, this paper presents a novel sports ads value evaluation method based on consumer psychology. Firstly, a reasonable evaluation index system (EIS) was established, and the index data were processed by principal component analysis (PCA) based on consumer psychology. Next, Schwartz-Moon model was extended into a sports ads value evaluation model in the light of consumer psychology and applied to evaluate sports ads value through numerical simulation. Our model and EIS were proved effective through experiments.